Pengetahuan Akuntansi dan Pengalaman Usaha terhadap Penggunaan Informasi Akuntansi (Studi Pelaku UKM Di Desa Wonokarto, Kec. Sekampung, Kab. Lam Tim) - Nur Faja Surta Berliana; Lella Anita; Era Yudistira; Witantri Dwi Swandini (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The purpose of this study is to identify and analyze the influence of accounting knowledge and business experience on the use of accounting information by MSME in Wonokarto Village. This research utilizes primary data collected through the questionnaires to a sample of 40 business actors who apply accounting information. The data analysis method used is multiple linear regression analysis with SPSS version 25 software. The results of this study indicate that both accounting knowledge and business experience significantly affect the use of accounting information by business actors. This study also acknowledges the limitations in the scope of variables examined. Other factors such as education level, business age, work motivation, and additional aspects need to be studied more deeply to obtain a more comprehensive understanding.